PENGARUH STRATEGI PQ4R TERHADAP HASIL BELAJAR MATERI MINYAK BUMI SMA NEGERI 2 SINGINGI - Wahidatun Muharomah; Asregi Asril; Rosa Murwindra (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This study aims to determine student learning outcomes in petroleum material in class XI IPA 2 Singingi State High School. The sampling technique is the cluster random sampling technique. The sample in this study was class XI IPA1 as a control class andclass XI IPA2 as an experimental class. The test instruments used in this study were content validity that was judged by 3 experts, item analysis and question reliability and analyzed using ANATES. Data collection techniques in this study were written testtechniques in the form of multiple choice with 20 items. To test the hypothesis is done using nonparametric statistics namely Mann-Whitney Utest. Based on the nonparametric test analysis results obtained sig. Value (1-tailed) 0.001 < 0.05, then H0 is rejected and HI is accepted. So it can be concluded that the learning outcomes using the PQ4R strategy are better than using conventional learning in class XI IPA of SMA Negeri 2 Singingi on petroleum material.